Pengalaman Seksualitas Ibu Hamil di Puskesmas Pondok Aren Tangerang - Vike Dwi Hapsari; Sari Sudarmiati (Jurnal Ners, 2011)
Introduction: Pregnancy is an important event in women life. Various physical and psychological changes may affect pregnant women, particularly on sexuality. Along with the growing size of uterus in pregnant women, it can lead to discomfort and diffi culty for sexual intercourse. The aimed of this tudy was to understand sexuality experience among pregnant women. Methods: This was qualitative research with phenomenological approach. Five participants involved in this study using purposive sampling. Data was collected with an indepth interview and then was analyzed with Colaizzi’s. This research was emerged six themes. The meaning of sexuality, changes of sexuality, cause of sexuality changes in intimate relationship, the reason for doing intercourse, partner caring, and myth about sexuallity in pregnan women.Result: The results showed pregnant women have difefrence sexuality experience from the step trimester. Discussion: This research concludes that a nurse needs to give information to women and their family especially her husband regarding sexuality changes in pregnant women.